ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP MINAT MASYARAKAT DALAM PEMBIAYAAN RUMAH DENGAN PRINSIP SYARIAH - Aliya Cahyani Purnaed; Tubagus Rifqy Thantawi; Ermi Suryani (SAHID BANKING JOURNAL, 2022)
Owning a home is a need and a dream for every human being, with a home the family will grow well in it. Like a mirror in the house is a reflection of the human person. Owning a home can go through the world of Islamic banking, and Islamic banking must be able to attract people's interest in using its products. By providing a variety of prices, strategic housing with industrial and economic centers, as well as promotions that have been carried out are able to attract public interest in financing based on sharia principles through the world of sharia banking. This study aims to analyze the factors of product, price, place, promotion of public interest in home financing with sharia principles. This type of research is quantitative and the data collection method uses primary data obtained through questionnaires. Sampling of 100 respondents using the Tabachic and Fidell techniques, the sampling technique used simple random sampling technique. The method used to test the hypothesis is multiple linear regression, t test, f test and the coefficient of determination (adjusted R square). The results of this study indicate that price, place, and promotion affect people's interest in home financing with sharia principles. Meanwhile, these products have no effect on people's interest in home financing with sharia principles.